Apostenus ducati (Araneae: Liocranidae) sp. nov.: a second Nearctic species in the genus - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2013)
Apostenus ducati sp. nov. is described from montane areas in or adjacent to the Columbia River Basin of southeastern British Columbia in Canada and northern Washington and northwestern Montana in the United States. This is the second Nearctic species of this primarily Palaearctic genus. Unlike most liocranids, A. ducati apparently is restricted to open rocky habitats, such as talus and scree slopes, and on mountain peaks. Throughout most of its range, specimens occur in low numbers and populations are patchily distributed. Also, populations appear to be concentrated in the upper regions of the Flathead River watershed in British Columbia, an area of significant and competing ecological and economic values. Because of these factors, A. ducati is potentially a species of conservation concern.